Retrospective epidemiological analysis of pulmonary tuberculosis in the older adult and characterization of rifampicin resistance-associated rpoB mutations in Nantong City, China (2014–2023) - Huiming Zhu; Shouwei Wang; Xiaofang Zhao; Peipei Wu; Ji Chen; Feng Li (Frontiers in Public Health)
ObjectiveTo analyze the prevalence trend of older adult pulmonary tuberculosis (ETB) and the distribution and outcome of rifampicin-resistant rpoB gene mutation in ETB patients in Nantong.MethodsThe pulmonary tuberculosis patients’ data in Nantong from 2014 to 2023 were from Tuberculosis Information Management Syste and ETB and rifampicin-resistant rpoB mutation patients were retrospectively analyzed.ResultsFrom 2014 to 2023, the overall standardized incidence of ETB in Nantong showed a trend of rapid decline and tended to a stable trend stabilized. A total of 140 older adult patients with rifampin resistance, aged 60–69 years, 87 cases (62.1%). single-gene mutation Probe E mutations were the most frequent, observed in 39 cases (60.0%). Specifically, 52 cases (80.00%) were resistant to rifampicin, and Probe E of 31 cases (59.62%) showed the most mutations. The outcome of ETB patients with rifampicin resistance were significantly correlated with treatment classification, rifampicin resistance, Xpert MTB first test, and 0-month sequential sputum positivity.ConclusionThe number of ETB in Nantong from 2014 to 2023 showed a rapid decline and stabilized. The rpoB mutations in the ETB rifampicin-resistant patients were mainly single-gene mutations. The authorities should formulate effective regional prevention and control measures based on the characteristics of the ETB rifampicin-resistant patients.